Pengaruh Tingkat Hutang, Ukuran Perusahaan, Volatilitas Penjualan, Terhadap Persistensi Laba Pada Perusahaan Infrastruktur Yang Terdaftar Di Bursa Efek Indonesia - Dame Ria Rananta Saragi; Halomoan Sihombing; Juliana Novelentina Manurung (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (JEBMA), 2023)
This study aims to determine the effect of debt levels, company size, sales volatility on earnings persistence. The population in this study are infrastructure companies listed on the Indonesia Stock Exchange for the 2018-2021 period. The sample in this study was determined using a purposive sampling method. The selected samples were 16 companies with 4 periods or the same as the 64 samples used in this study. The data analysis method used in this study is multiple linear regression analysis. Based on the results of testing the hypothesis, it can be concluded that partially the level of debt has an effect on earnings persistence, while firm size has an effect on firm size, and sales volatility shows a negative relationship, meaning that sales volatility has no effect on earnings persistence.